Multidimensional study on special component plan schemes for the scheduled caste farm families - Rajendralal T V (Department of Agricultural Extension, College of Agriculture, 1997)
The present study under the title "Multidimensional study on Special Component Plan schemes for the scheduled caste farm families" was undertaken to assess the perception and attitude of scheduled caste farm families towards the S.C.P. schemes of the Department of Agriculture, Kerala and also to assess the acceptance of S.C.P. scheme by the scheduled caste families. The factors influencing the perception and attitude of scheduled castes towards the S.C.P. scheme and acceptance of S.C.P. schemes by the scheduled castes and constraints perceived by the scheduled castes in the acceptance of S.C.P. scheme were also assessed in the study. Two hundred numbers of scheduled caste of different I.H.D.P. habitats from 7 Krishi Bhavans in Palakkad District who were the beneficiaries of the S. C. P. scheme of Agriculture Department in the year 1994-95 were selected as the respondents for the study. Data were collected using interview schedule and suitable statistical techniques were employed in the analysis of data. Four major schemes under Special Component Plan namely the scheme for distribution of coconut seedlings, scheme for distribution of pepper cuttings, scheme for distribution of agricultural implements and scheme for distribution of vegetable seeds were selected for detailed study. The result of the perception of scheduled castes about the total S.C.P. scheme revealed that